Prediction of Cerebral Palsy or Death among Preterm Infants Who Survive the Neonatal Period - Peaceman, Alan M.; Mele, Lisa; Rouse, Dwight J.; Leveno, Kenneth J.; Mercer, Brian M.; Varner, Michael W.; Reddy, Uma M.; Wapner, Ronald J.; Sorokin, Yoram; Thorp, John M.; Ramin, Susan M.; Malone, Fergal D.; O'Sullivan, Mary J.; Dudley, Donald J.; Caritis, Steve N.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units Network (American Journal of Perinatology, 2022)
Objective To assess whether neonatal morbidities evident by the time of hospital discharge are associated with subsequent cerebral palsy (CP) or death.Study Design This is a secondary analysis of data from a multicenter placebo-controlled trial of magnesium sulfate for the prevention of CP. The association between prespecified intermediate neonatal outcomes (n = 11) and demographic and clinical factors (n = 10) evident by the time of discharge among surviving infants (n = 1889) and the primary outcome of death or moderate/severe CP at age 2 (n = 73) was estimated, and a prediction model was created.Results Gestational age in weeks at delivery (odds ratio [OR]: 0.74, 95% confidence interval [CI]: 0.67–0.83), grade III or IV intraventricular hemorrhage (IVH) (OR: 5.3, CI: 2.1–13.1), periventricular leukomalacia (PVL) (OR: 46.4, CI: 20.6–104.6), and male gender (OR: 2.5, CI: 1.4–4.5) were associated with death or moderate/severe CP by age 2. Outcomes not significantly associated with the primary outcome included respiratory distress syndrome, bronchopulmonary dysplasia, seizure, necrotizing enterocolitis, neonatal hypotension, 5-minute Apgar score, sepsis, and retinopathy of prematurity. Using all patients, the receiver operating characteristic curve for the final prediction model had an area under the curve of 0.84 (CI: 0.78–0.89). Using these data, the risk of death or developing CP by age 2 can be calculated for individual surviving infants.Conclusion IVH and PVL were the only neonatal complications evident at discharge that contributed to an individual infant's risk of the long-term outcomes of death or CP by age 2. A model that includes these morbidities, gestational age at delivery, and gender is predictive of subsequent neurologic sequelae.Key Points
Keywords: cerebral palsy; magnesium sulfate; premature rupture